2019
DOI: 10.1002/ejic.201900667
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic Synthesis of Ammonia from Water and Air in a Membrane‐Free Cell: Confining the Iron Oxide Catalyst to the Cathode

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…The standard electrode potential (or reduction potential) of ferrous ions obtained from electron loss was 0.44 V. [20] Thus, as the iron electrodes were loaded with a potential over 0.44 V, the oxidation reaction could occur at the anode as follows (see middle images in Figure 1b): Fe − 2e − = Fe 2+ , where Fe 2+ ions were further oxidized by oxygen (from air) into Fe 3+ ions through the reaction of 4Fe 2+ + O 2 + 4H + = 4Fe 3+ + 2H 2 . [21] The cathode reaction did not generate metal ions, but giving rise to hydroxyl ions by following the chemical reaction: [22] Driven by the difference of potential, Fe 3+ ions migrated toward the cathode, and OH − shifted to the anode, resulting in the reaction of Fe 3+ + 3OH − = Fe(OH) 3 , which turned hydrogel into reddish-brown color, and elicited physical interaction with PAAm matrix (right image in Figure 1b, and more details will be discussed below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard electrode potential (or reduction potential) of ferrous ions obtained from electron loss was 0.44 V. [20] Thus, as the iron electrodes were loaded with a potential over 0.44 V, the oxidation reaction could occur at the anode as follows (see middle images in Figure 1b): Fe − 2e − = Fe 2+ , where Fe 2+ ions were further oxidized by oxygen (from air) into Fe 3+ ions through the reaction of 4Fe 2+ + O 2 + 4H + = 4Fe 3+ + 2H 2 . [21] The cathode reaction did not generate metal ions, but giving rise to hydroxyl ions by following the chemical reaction: [22] Driven by the difference of potential, Fe 3+ ions migrated toward the cathode, and OH − shifted to the anode, resulting in the reaction of Fe 3+ + 3OH − = Fe(OH) 3 , which turned hydrogel into reddish-brown color, and elicited physical interaction with PAAm matrix (right image in Figure 1b, and more details will be discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…[21] The cathode reaction did not generate metal ions, but giving rise to hydroxyl ions by following the chemical reaction: O 2 + 2H 2 O + 4e − = 4OH − . [22] Driven by the difference of potential, Fe 3+ ions migrated toward the cathode, and OH − shifted to the anode, resulting in the reaction of Fe 3+ + 3OH − = Fe(OH) 3 , which turned hydrogel into reddish-brown color, and elicited physical interaction with PAAm matrix (right image in Figure 1b, and more details will be discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…A further attempt at STEP-ammonia was launched by Licht and his co-workers. [66][67][68] They emphasized that nano-Fe 2 O 3 loaded on activated carbon (Fe 2 O 3 AC) achieves superior dispersion and effectively inhibits HER. The NH 3 yield rate of 8.27 Â 10 À9 mol s À1 cm À2 was obtained at a current density of 49 mA cm À2 .…”
Section: Electrode Engineeringmentioning
confidence: 99%
“…9 Confining the iron oxide catalyst to the cathode, to prevent the reoxidation of iron at the anode, can further improve ammonia production. 10 With respect to the promising results on the current efficiency and reaction rate in STEP ammonia, the durability and sustainability of the reaction system still need improvement to compete with the industrial process.…”
Section: Step For Carbon Neutral Productsmentioning
confidence: 99%
“…It was found that the Fe 2 O 3 /AC not only inhibits the hydrogen evolution reaction (HER) but also prevents the Fe 2 O 3 nanoparticles from aggregation, resulting in a high ammonia production rate of 8.27 × 10 –9 mol s –1 cm –2 at 250 °C with a current density of 49 mA/cm 2 . Confining the iron oxide catalyst to the cathode, to prevent the reoxidation of iron at the anode, can further improve ammonia production …”
Section: Step For Carbon Neutral Productsmentioning
confidence: 99%